The Process of Constructing the Female Self in Family: Rethinking About Sacricity of Family and Indecency of Divorce (Case Study of Women from University of Tehran) - Zahra Aghajani; Jahangir Jahangiri; abdolali lahsaeizadeh (توسعه اجتماعی)
Divorce, especially in transitional societies like Iran, that hallow the family, is not only as a moral evil but as a factor of loss and harm. The results shows that this representation in some case is an unfounded stereotype which needs revisions. Structural changes in societies from traditional to modern conditions, leads to the wide changes in dominant values. The most important changes include the rise of ethical values such as autonomy and individuality which explained in Emmanuel Kant philosophy. These fundamental principles are the basis for defining the "personal identity" in modern society according to Anthony Giddens. This work shows how the divorce experience leads to the substantiation of these moral principles and consequently personal identity. We work with 21 middle class women who educated in social sciences. Our method is Grounded Theory for understanding the “process of constructing Identity”, but during our research we faced with troubles arised from its methodological requirements and assumptions, which was an obstacle to the realistic interpretations of the data. Grounded Theory practically, distorts data confrontation, which is incompatible with sociologic purposes.